Analisis Pengendalian Intern pada Sistem Penjualan dan Persediaan (Studi Kasus Perusahaan Dagang Frozen Food Prima Freshmart) - Naila mutiara Azza deanjani; Afridian Wirahadi Ahmad (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2025)
The study was conducted to analyze the implementation of the Internal Control System (ISC) in the sales and inventory system at the Frozen Food trading company Prima Fresh mart. The focus of the study is to evaluate the implementation and compliance with the Standard Operating Procedure (SOP) of the Internal Control System (SSC) as part of the operational risk management strategy. This research method uses qualitative descriptive research with interview and observation techniques with employees. From this study, the results of the study indicate that although the SOP has been created as an operational guide, there are still several weaknesses in the implementation of the SOP that affect the effectiveness of internal control. Such as analyzing delays in making inventory reports and suboptimal staff understanding. This has an impact on the risk of recording errors, stock discrepancies, and lack of efficiency in the sales process.